2014
DOI: 10.1007/s00134-014-3287-7
|View full text |Cite
|
Sign up to set email alerts
|

Dysglycaemia in the critically ill and the interaction of chronic and acute glycaemia with mortality

Abstract: Critical illness-associated hyperglycaemia is the most frequent cause of hyperglycaemia in the critically ill. Peak glucose concentrations during critical illness are associated with increased mortality in patients with adequate premorbid glycaemic control, but not in patients with premorbid hyperglycaemia. Optimal glucose thresholds in the critically ill may, therefore, be affected by premorbid glycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 35 publications
6
132
0
1
Order By: Relevance
“…In a prospective study on 1,000 consecutive patients admitted in an intensive care unit, each 1 mmol/l increase in peak blood glucose during the first 48 hours was associated with a 20% increase in risk of death in patients with critical illness-associated hyperglycemia and in those with established diabetes and HbA1c levels <7 % [21]. In a group of 134 patients who survived to hospital admission after an OHCA, in those who were alive at discharge blood glucose levels remained stable between pre-hospital and admission, while in non-survivors there was a significant increase between these 2 time points [22].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study on 1,000 consecutive patients admitted in an intensive care unit, each 1 mmol/l increase in peak blood glucose during the first 48 hours was associated with a 20% increase in risk of death in patients with critical illness-associated hyperglycemia and in those with established diabetes and HbA1c levels <7 % [21]. In a group of 134 patients who survived to hospital admission after an OHCA, in those who were alive at discharge blood glucose levels remained stable between pre-hospital and admission, while in non-survivors there was a significant increase between these 2 time points [22].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological background for this apparent difference is unclear. Other observational studies have suggested that the optimal glycemic target in diabetics may depend on the pre-existing level of glycemic control, as reflected by the pre-admission HbA1c (20,21). From a physiological point of view, this appears more plausible, as patients may adapt to chronic hyperglycemia (22).…”
Section: Editorialmentioning
confidence: 99%
“…[51][52][53][54] Consequently, strict adherence to a protocol for glycemic control is pivotal. 55 The effect of an educational intervention on ICU nurses' knowledge about glycemic control was assessed by means of a beforeafter study.…”
Section: Agitation Confusion and Deliriummentioning
confidence: 99%